Pilot study protocol of a randomized controlled trial for the potential effects of creatine monohydrate on persistent post-concussive symptoms - Bødker, Ronni Lykke; Marcussen, Michael (Frontiers in Neurology, 2023)
Background: Mild traumatic brain injury or concussion is a global public concern, with an estimated annual incidence between million and 96 million worldwide. It is a socioeconomical problem, and almost onethird of individuals with concussion suffer from severe persistent post-concussive symptoms (PPCS), with an increased risk of unemployment or terminating their studies. To date, no single treatment is available with guaranteed success. Creatine monohydrate (CrM) has shown potential as a treatment for postconcussive symptoms, having a positive impact on cognitive function, chronic fatigue, depression, and anxiety. The aim of this study is to examine the effect of CrM on PPCS assessed using the Rivermead Post-Concussion Symptoms Questionnaire (RPQ). Methods: The study is designed as a double-blinded randomised controlled trial. Study participants are found through neurological outpatient clinics in Denmark or through social media. They will be between 25 and 35 years of age, will have suffered from PPCS for 6 to 12 months prior to inclusion, and will have no comorbidities. The participants will be randomly allocated to either an intervention group (INT), placebo group (PLA), or control group (CG). Baseline data will be collected immediately after inclusion, and the study period will be 7 weeks. Follow-up data will be collected 1 week after the end of the study period. The primary outcome of the study is changes in RPQ score. Changes in weight and training status will be adjusted for as potential confounders. Ethics and dissemination: This protocol is approved by the National Committee on Health Research (97508) and by the Danish Data Protection Agency 11.651. The investigators intend to submit their study findings for publication in peer-reviewed journals and disseminate the findings via presentation at academic meetings/conferences. Trial registration number: NCT05562232. Registered